Meningkatkan Kemampuan Membaca Anak Melalui Penerapan Metode Drill And Practice - Octaviani, Srikandi; Sufianti, Alif Via (Indonesian Research Journal on Education, 2022)
A common mistake that adults make when teaching children to read is to place more emphasis on memorizing the consonants of the alphabet from A to Z, so that even though the child has memorized the letters, the child will still have difficulty reading and become confused when faced with text or example sentences. One method that can be used to introduce reading to children is to use the drill and practice method. Of the 15 Kindergarten A children, only 3 people can correctly pronounce the letters A, B, C to Z, but cannot pronounce the sound when 2-3 letters are combined into words, 5 people can point to some letters at random but not all the letters can correctly mentioned only a few letters at random, and as many as 7 children only memorized thepronunciation without knowing the shape of the letters called. The reflection of the application ofthe drill and practice method is that repeated exercises are indeed needed, because of the limited time to study in school, plus the focus of children who are easily divided, making it difficult for children to concentrate on books, with repeated exercises, children's memory becomes more embedded. The results of this study are an increase in children's reading skills through theapplication of the Drill and Practice method, from children who can only say letters without knowing how the symbols or letter shapes are to become children who can not only mention letters one by one but also mention the sound of the letters that are connected to form a word, from a child who only knows a few random letter symbols to a child who is able to name every consonant of a letter with the right sound.